Penggunaan Cerita Jataka Melalui Platform Digital dalam Pembelajaran di Sekolah Minggu Buddha - Latifah, Latifah (University of Brawijaya, 2024)
In the digital era, the transmission of spiritual values through online platforms has become increasingly vital, particularly in religious education for Buddhist Sunday Schools. Jataka tales, which recount the past lives of the Buddha, hold significant potential for instilling Buddhist values in learners. However, the adaptation and effective delivery of these stories via digital platforms remain underexplored. This study aims to describe and analyze the use of Jataka tales through digital platforms—specifically the YouTube channels Dhamma Metta Jember, Guna Dharma, and SMB Sikkhadama Santibhumi—in the context of Buddhist Sunday School education. Employing a qualitative content analysis approach, the study investigates the types of Jataka tales utilized and the methods of their online delivery. The findings reveal that digital platforms have become instrumental in imparting Buddhist values to children and adolescents through creatively adapted Jataka tales. This research contributes to the development of more relevant religious education strategies in the digital age and highlights the role of literature in character education. In conclusion, classical tales such as the Jataka can serve as powerful tools for moral and ethical development through innovative digital approaches.